Trace nitrogen-doped amorphous oxyhalide solid-state electrolyte, preparation method and application thereof
Patent Information
- Application Number
- CN202611158125.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-16
AI Technical Summary
[0008]本发明的目的在于提供一种痕量氮掺杂非晶卤氧化物固态电解质及其制备方法和应用,用以解决现有方法难以实现在保持卤氧化物非晶特征和低电子电导的同时,通过少量含氮组分实现钠离子传输性能可控调节的材料组成的技术问题
本发明公开了一种痕量氮掺杂非晶卤氧化物固态电解质,其阴离子位点由O2-和N3-共同占据,且N3-的掺杂量x满足0<x≤0.12,化学通式为Na2Li3xMClyO2Nx,其中M选自Hf、Ta、Zr、Al或Nb中的至少一种,3≤y≤5。相对于现有Na2MClyO2基非晶卤氧化物材料,本发明通过N3-对O2-位点的痕量掺杂,使N3-与O2-共同占据阴离子位点,改变了材料中金属中心周围的阴离子配位环境,破坏了部分桥氧键,增加了非晶基体的结构无序程度,从而降低了钠离子迁移的能垒;同时,由于N3-掺杂量被严格控制在0<x≤0.12的痕量范围,可有效避免过量氮掺杂可能引发的局部结构畸变或副产物生成,从而在保持卤氧化物非晶特征和低电子电导的前提下,实现了钠离子传输性能的可控调节。有效解决了现有技术难以在保持非晶卤氧化物低电子电导的同时通过含氮组分实现钠离子传输性能可控调节的难题。
Smart Images

Figure CN122931012A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state battery technology, specifically relating to a trace nitrogen-doped amorphous halide oxide solid electrolyte, its preparation method, and its application. Background Technology
[0002] All-solid-state sodium batteries use a solid electrolyte instead of traditional flammable organic electrolytes, fundamentally reducing the risks of electrolyte leakage and thermal runaway. Simultaneously, sodium is abundant and widely distributed in the Earth's crust, giving this system significant cost competitiveness in large-scale energy storage. In all-solid-state sodium batteries, the solid electrolyte plays a dual crucial role: serving as a medium for conducting sodium ions and physically isolating the positive and negative electrodes while providing a stable ion transport environment for electrochemical reactions. Therefore, the ionic conductivity and electronic insulation properties of the electrolyte directly constrain the battery's polarization behavior, rate performance, and long-term cycle stability.
[0003] Unlike liquid electrolytes, solid-state electrolytes require ions to migrate continuously within the solid and at the electrode / electrolyte contact area. Therefore, in addition to high room-temperature sodium ion conductivity, materials should minimize electronic conductivity and maintain effective solid-solid contact during pressing and cycling. Grain boundaries, localized compositional segregation, and insufficient contact between the electrode and electrolyte can all increase ion migration resistance, making it difficult to fully utilize the intrinsic conductivity of the material in practical batteries.
[0004] Halide materials in inorganic solid electrolytes typically exhibit good formability and high-voltage adaptability, attracting widespread attention in recent years. However, the relatively fixed coordination structure and grain boundaries in crystalline halides may limit the rapid migration of sodium ions, and some materials may undergo structural or compositional changes at the electrode interface. Introducing oxygen into halides and constructing halide oxides can alter the anion coordination environment around the metal center and facilitate the formation of disordered structures, providing a new approach to modulating the ion transport and chemical stability of the materials.
[0005] Compared to crystalline materials, amorphous halide oxides lack long-range ordered lattices and clear grain boundaries, offering greater tunability in their local coordination environment and free volume distribution. Mechanochemical methods can promote mixing, reaction, and amorphization of raw materials at lower temperatures, avoiding crystallization or component loss that may occur during high-temperature processing. Therefore, they are suitable for preparing water- and oxygen-sensitive halide oxide solid electrolytes. However, the amorphous structure itself does not necessarily result in higher ionic conductivity; the local bonding mode, anion composition, defect concentration, and degree of amorphization still collectively determine the sodium ion migration barrier.
[0006] Amorphous halide oxides, represented by the Na-M-Cl-O system, possess the characteristic of forming stable metal-oxygen coordination structures and can be obtained as amorphous products through mechanochemical processes. However, the local structures available for sodium ion migration in existing compositions still have room for further regulation. Simply changing the ball milling conditions or increasing the degree of disorder is insufficient to guarantee a continuous improvement in ion transport performance; if the anion environment is not sufficiently regulated, the material may still exhibit high migration resistance, while excessive modification of the local coordination structure may disrupt the favorable transport network. Therefore, it is necessary to study the relationship between the local chemical environment and sodium ion transport performance in amorphous matrices from the perspective of trace component regulation.
[0007] The introduction of nitrogen-containing components can alter the local bonding and charge compensation mechanisms in materials, but their effect in amorphous halide oxides is influenced by various factors, including the amount added, the degree of reaction, and the amorphous network structure. Insufficient addition may hinder effective regulation, while excessive addition may lead to the formation of local structures or byproducts that impede sodium ion migration. Currently, there is a lack of material compositions and preparation methods that can achieve controllable regulation of sodium ion transport performance through a small amount of nitrogen-containing components while maintaining the amorphous characteristics and low electronic conductivity of halide oxides. Summary of the Invention
[0008] The purpose of this invention is to provide a trace nitrogen-doped amorphous halide oxide solid electrolyte, its preparation method, and its application, in order to solve the technical problem that existing methods are unable to achieve a material composition in which sodium ion transport performance can be controlled and adjusted by a small amount of nitrogen-containing components while maintaining the amorphous characteristics and low electronic conductivity of halide oxides.
[0009] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a trace nitrogen-doped amorphous halide oxide solid electrolyte, wherein the solid electrolyte is an amorphous material, and the anion sites of the solid electrolyte are composed of O 2- and N 3- Jointly occupied, and N 3- The doping amount x satisfies 0 <x≤0.12; The chemical formula of the solid electrolyte is Na₂Li. 3x MCl y O2N x M is selected from at least one of Hf, Ta, Zr, Al or Nb, and 3≤y≤5.
[0010] Furthermore, the ionic conductivity of the solid electrolyte at room temperature is not less than 5 × 10⁻⁶. -4 S / cm, electronic conductivity less than 9×10 -10 S / cm, activation energy below 0.33 eV.
[0011] Further, the ionic conductivity of the solid electrolyte at room temperature is not less than 8×10 -4 S / cm, and the electronic conductivity is lower than 6.1×10 -10 S / cm, the activation energy is lower than 0.32 eV, the Young's modulus is lower than 2.8 GPa, and the electrochemical stability window is greater than 4.3 V.
[0012] The present invention also discloses a preparation method of the above trace nitrogen-doped amorphous oxyhalide solid electrolyte, comprising the following steps: Weigh the sodium source, M source, chlorine source, oxygen source and nitrogen source as raw materials according to the chemical general formula Na2Li 3x MCl y O2N x mix the weighed raw materials, and perform ball milling treatment under inert atmosphere or vacuum protection to obtain the trace nitrogen-doped amorphous oxyhalide solid electrolyte.
[0013] Further, the sodium source is Na2O2; the M source is at least one of HfCl4, TaCl5, ZrCl4, AlCl3 and NbCl5.
[0014] Further, the nitrogen source is Li3N; the oxygen source is Na2O2.
[0015] Further, the chlorine source is MCl y , where 3≤y≤5.
[0016] Further, the rotation speed of the ball milling treatment is 200~1000 rpm, and the time is 5 minutes~72 hours.
[0017] Further, the ball milling treatment is intermittent ball milling, and the machine is stopped and left to stand for 5 minutes every 5 minutes of ball milling.
[0018] The present invention also discloses the application of the above trace nitrogen-doped amorphous oxyhalide solid electrolyte in an all-solid-state battery.
[0019] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a trace nitrogen-doped amorphous oxyhalide solid electrolyte, the anion sites of which are jointly occupied by O 2- and N 3- , and the doping amount x of N 3- satisfies 0<x≤0.12, with the chemical general formula of Na2Li 3x MCl y O2N x , wherein M is selected from at least one of Hf, Ta, Zr, Al or Nb, and 3≤y≤5. Compared with the existing Na2MCl y O2-based amorphous oxyhalide materials, the present invention adopts N3- O 2- sites by trace doping allows N 3- and O 2- to jointly occupy the anion sites, which changes the anion coordination environment around the metal center in the material, breaks part of the bridging oxygen bonds, increases the structural disorder degree of the amorphous matrix, and thus reduces the energy barrier for sodium ion migration; at the same time, since the doping amount of N 3- is strictly controlled in a trace range of 0<x≤0.12, local structural distortion or by-product formation that may be caused by excessive nitrogen doping can be effectively avoided, so that the controllable adjustment of sodium ion transport performance is realized on the premise of maintaining the amorphous characteristics and low electronic conductivity of the oxyhalide. The invention effectively solves the problem in the prior art that it is difficult to realize the controllable adjustment of sodium ion transport performance through nitrogen-containing components while maintaining the low electronic conductivity of the amorphous oxyhalide.
[0020] Further, the ionic conductivity of the solid electrolyte at room temperature is not less than 5×10 -4 S / cm, and a preferred embodiment can reach 8×10 -4 S / cm or more, with an activation energy lower than 0.33eV, and an electrochemical stability window greater than 4.3V (vs. Na 15 Sn₄), and a Young's modulus lower than 2.8GPa, which combines high ionic conductivity, good interfacial stability and good mechanical properties.
[0021] Further, trace N 3- can adjust the local anion environment and structural disorder degree of the amorphous matrix, thereby changing the migration conditions of sodium ions, so that the obtained electrolyte has high room-temperature ionic conductivity; the all-solid-state sodium battery assembled with this electrolyte also shows certain cycle stability and rate performance, indicating that it has good compatibility with electrode materials. In addition, the amorphous characteristic of the material is beneficial to compaction and densification, and can improve the solid-solid contact between the electrolyte and the electrode.
[0022] This invention also discloses a method for preparing the aforementioned trace nitrogen-doped amorphous halide oxide solid electrolyte. The method involves ball milling under an inert atmosphere or vacuum protection, utilizing the mechanical energy input during milling to promote solid-state reactions between raw materials and gradually form a non-long-range ordered structure in the reaction products. This allows for the direct acquisition of the trace nitrogen-doped amorphous halide oxide solid electrolyte without subsequent high-temperature sintering. This method eliminates the need for high-temperature heat treatment, effectively avoiding crystallization or component volatilization losses that may occur during high-temperature processing, thus ensuring the stable formation of the amorphous structure and precise controllability of trace nitrogen doping. Furthermore, the process flow of raw material weighing, mixing, and ball milling is short and simple, facilitating large-scale preparation and suitable for the synthesis of halide oxide solid electrolytes sensitive to water and oxygen. The method achieves mixing, solid-state reaction, and amorphization simultaneously in a single ball milling step, avoiding complex multi-step processes. Moreover, the reaction progress and degree of amorphization can be effectively controlled by adjusting the ball milling speed and time, flexibly matching the preparation requirements of different composition systems. Attached Figure Description
[0023] Figure 1 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 XRD patterns; Figure 2 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 Electrochemical impedance spectroscopy; Figure 3 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 ionic conductivity diagram; Figure 4 Na2ZrCl4O2, Na2Li 0.09 ZrCl4O2N 0.03 NaTaCl5O, NaLi 0.21 TaCl5ON 0.07 Na2NbCl5O2, Na2Li0.21 NbCl5O2N 0.07 ionic conductivity diagram; Figure 5 Na2HfCl4O2, Na2Li 0.21 HfCl4O2N 0.07 Electrochemical stability window diagram; Figure 6 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 The graph showing the relationship between ionic conductivity and temperature, and the calculated activation energy value; Figure 7 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 Electron conductivity diagram; Figure 8 Na₂Li at a current density of 0.5C 0.21 HfCl4O2N 0.07 Electrochemical performance; Figure 9 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 Rate performance. Detailed Implementation
[0024] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0025] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0026] In this document, all features defined in the form of numerical ranges or percentage ranges, such as values, amounts, contents and concentrations, are provided merely for brevity and convenience. Accordingly, the description of a numerical range or percentage range shall be deemed to have specifically disclosed and covered all possible subranges and individual values within the range, including integers and fractions.
[0027] In this document, unless otherwise specified, the terms "comprising", "including", "containing", "having" or similar expressions cover the meanings of "consisting of" and "consisting essentially of". For example, the expression "A comprises a" covers the meanings of "A comprises a and other components" and "A consists only of a".
[0028] In this document, for the sake of concise description, all possible combinations of various technical features in each implementation solution or embodiment are not described. Therefore, as long as there is no contradiction in the combinations of these technical features, the various technical features in each implementation solution or embodiment can be combined arbitrarily, and all possible combinations shall be regarded as the scope recorded in this specification.
[0029] The present invention provides a trace nitrogen-doped amorphous oxyhalide solid electrolyte, through N 3- trace-doped hafnium-based oxyhalide amorphous solid electrolyte. In the matrix of Na₂HfCl₄O₂, through N 3- partial substitution of O 2- sites, an amorphous material with the general formula of Na₂Li 0.21 HfCl₄O₂N 0.07 is formed. N 3- substitutes for part of O 2- , breaks the bridging oxygen bonds, increases the degree of structural disorder, and finally the Na₂Li 0.21 HfCl₄O₂N 0.07 amorphous material has both high ionic conductivity, good interfacial stability and good mechanical properties.
[0030] The present invention uses mechanical ball milling to promote raw material mixing, solid-phase reaction and amorphization, and the target electrolyte can be obtained under a protective atmosphere without a subsequent sintering process. The process parameters of this method can be adjusted through the ball milling rotation speed, treatment time and intermittent procedure. Specifically, the method includes the following steps: During preparation, first calculate the dosages of the sodium source, M source, chlorine source, oxygen source and Li₃N according to the target composition of Na₂Li 3x MCl y O₂N x , where M is selected from Hf, Ta, Zr, Al or Nb, 0<x≤0.12, 3≤y≤5. The weighed raw materials are placed in a ball milling tank and sealed, and the loading and sealing processes are carried out under inert atmosphere or vacuum protection conditions, and then mechanical ball milling is used to make the raw materials undergo mixing, solid-phase reaction and amorphization; Preferably, the sodium source is Na2O2; The M source is at least one of HfCl4, TaCl5, ZrCl4, AlCl3, and NbCl5.
[0031] The nitrogen source is Li3N; The oxygen source is Na2O2; The chlorine source is MCl. y , where 3≤y≤5.
[0032] Preferably, the ball milling process is performed at a rotation speed of 200-1000 rpm for 5 minutes to 72 hours.
[0033] In some embodiments of the present invention, the specific chemical composition of the solid electrolyte is Na₂Li. 0.21 HfCl4O2N 0.07 After optimization and screening, this component was tested at room temperature using the blocked electrode method, and its sodium ion conductivity reached 8.1 × 10⁻⁶. -4 S / cm, electronic conductivity less than 6.1×10 -10 S / cm, activation energy below 0.32 eV. Linear sweep voltammetry indicates its electrochemical stability window is greater than 4.3 V (vs. Na). 15 Sn4). X-ray diffraction patterns show that it has a typical amorphous structure. Atomic force microscopy measured a Young's modulus of less than 2.8 GPa.
[0034] Na2Li 0.21 HfCl4O2N 0.07 Taking the preparation of [product name] as an example, in an argon glove box with H2O and O2 contents both below 0.01 ppm, Na2O2, HfCl4, and Li3N were weighed according to the stoichiometric relationship of the target product, with a total raw material mass of approximately 1.0 g per container. Zirconia grinding balls with a diameter of 5 mm were used, and the grinding balls and raw materials were prepared at a ball-to-material mass ratio of 40:1; after both were loaded into the zirconia ball mill jar, the ball mill jar was sealed inside the glove box.
[0035] The sealed ball mill jar operates at 500 rpm. The ball milling program consists of continuously repeating working and stopping segments: each segment involves 5 minutes of ball milling followed by a 5-minute resting period before starting the next cycle; the cumulative effective ball milling time for each segment is 8 hours. After ball milling, the powder in the jar is collected, and the resulting product is not subjected to sintering or other high-temperature heat treatment. Intermittent operation reduces the temperature rise caused by continuous ball milling, which helps maintain the amorphous state of the product.
[0036] In other embodiments, the rotational speed of ball milling can be selected within the range of 200 to 1000 revolutions per minute, the ball milling time can be adjusted within the range of 5 minutes to 72 hours, and an inert atmosphere or vacuum protection is maintained during the ball milling process.
[0037] A second aspect of the present invention provides an application example of the above solid electrolyte in an all-solid-state sodium battery. The solid electrolyte powder is pressed to form a dense electrolyte layer, and the electrolyte layer assumes the functions of sodium ion conduction and separation of the positive electrode and the negative electrode; a high-voltage oxide positive electrode of sodium nickel iron manganate is adopted as the battery positive electrode, and a sodium-tin alloy negative electrode is adopted as the negative electrode, so that the all-solid-state sodium battery is assembled. Tests show that the battery exhibits good rate performance and cycling stability.
[0038] The trace nitrogen-doped solid electrolyte of the present invention is an amorphous non-crystalline oxyhalide, and by adjusting N 3- doping ratio, the degree of structural disorder of the whole material can be adjusted, so that the material has high ionic conductivity, and further has good electrochemical performance, and the material has low activation energy.
[0039] More specifically, the present invention uses a Na₂MCl y O₂ (M= Hf, Ta, Zr, Al, Nb)-based electrolyte as a matrix, where 3≤y≤5. Through elaborate component design and ion substitution strategy, the nitrogen (N) element is innovatively introduced to partially substitute at the O 2- site, finally forming an amorphous material with a chemical general formula of Na₂Li 3x MCl y O₂N x (M= Hf, Ta, Zr, Al, Nb), where 0<x≤0.12, 3≤y≤5. This unique trace nitrogen-doped amorphous structure systematically optimizes the ion transport properties, interfacial stability and mechanical properties of the electrolyte through the synergistic effect among multiple elements.
[0040] From the perspective of material design mechanism analysis, the present invention achieves comprehensive improvement of the overall performance of the electrolyte through trace nitrogen doping. N 3- substitutes for part of O 2- , breaks part of the bridging oxygen bonds, increases the degree of structural disorder, and finally effectively improves Na₂Li 3x MCl y O₂N xIonic conductivity of amorphous materials (M= Hf, Ta, Zr, Al, Nb), where 0<x≤0.12, 3≤y≤5. The formation of the amorphous structure enhances the intrinsic flexibility of the material, optimizes the mechanical properties, and makes the material easier to achieve densification during cold press forming, thereby reducing grain boundary impedance and improving the solid-solid contact with the electrode material. Benefiting from this, the ionic conductivity of this solid electrolyte at room temperature is increased, while the electronic conductivity is effectively suppressed, ensuring good sodium ion selective conduction characteristics.
[0041] In terms of preparation process, the present invention provides a simple and efficient one-step mechanochemical synthesis method. Specifically, according to the chemical general formula, raw materials including a sodium source (Na2O2), an M source (at least one of HfCl4, TaCl5, ZrCl4, AlCl3 and NbCl5), and a chlorine source (MCl y , where 3≤y≤5), an oxygen source (Na2O2) and a nitrogen source (Li3N) are weighed. After mixing the raw materials, ball milling is carried out at 200~1000 rpm under an inert atmosphere or vacuum condition, and the treatment time is 5 minutes~72 hours. The mechanical energy input during the ball milling process can promote the solid-phase reaction between the raw materials, and make the reaction product gradually form a structure without long-range order, so as to obtain a trace nitrogen-doped amorphous oxyhalide solid electrolyte without subsequent high-temperature sintering. This preparation route has few steps, and the reaction and amorphization process can be controlled by adjusting the ball milling speed and time.
[0042] Through composition innovation, the present invention carries out fine modification on the Na2MCl y O2 (M= Hf, Ta, Zr, Al, Nb) based electrolyte, where 3≤y≤5. In the matrix of Na2MCl y O2 (M= Hf, Ta, Zr, Al, Nb), where 3≤y≤5, through partial substitution of N 3- for O 2- sites, an amorphous material with the general formula of Na2Li 3x MCl y O2N x (M= Hf, Ta, Zr, Al, Nb) is formed, where 0<x≤0.12, 3≤y≤5; due to the doping of trace Li3N, N 3- replaces part of O 2- , destroys part of the bridging oxygen bonds, increases the degree of structural disorder, and finally the Na2Li 3x MCl y O2N x (M= Hf, Ta, Zr, Al, Nb) amorphous material combines high ionic conductivity, good interface stability and good mechanical properties, where 0<x≤0.12, 3≤y≤5.
[0043] Preferably, trace amounts of N 3- The local anionic environment and structural disorder of the amorphous matrix can be adjusted, thereby altering the migration conditions of sodium ions and resulting in an electrolyte with high room-temperature ionic conductivity. All-solid-state sodium batteries assembled using this electrolyte also exhibit good cycle stability and rate performance, indicating good compatibility with electrode materials. Furthermore, the amorphous nature of the material facilitates compaction and improves the solid-solid contact between the electrolyte and the electrode.
[0044] This invention also discloses a method for preparing the above-mentioned trace nitrogen-doped amorphous halide oxide solid electrolyte. This method uses ball milling and is synthesized by a one-step mechanochemical method without the need for high-temperature sintering. It has the advantages of excellent comprehensive performance, simple preparation process, and applicability to all-solid-state sodium batteries.
[0045] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.
[0046] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications conventional in the art. In this specification and the following examples, unless otherwise specified, "%" refers to weight percentage, "parts" refers to parts by weight, and "ratio" refers to weight proportion.
[0047] Example 1 A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte includes the following steps: In this embodiment, Na₂O₂ was used as the sodium and oxygen source, HfCl₄ as the hafnium and chlorine source, and Li₃N as the nitrogen source to synthesize Na₂Li. 0.09 HfCl4O2N 0.03 ; Na2O2, HfCl4, and Li3N raw materials were weighed in a molar ratio of 1:1:0.03 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at 500 rpm for 8 hours. During the ball milling process, the mill was stopped for 5 minutes every 5 minutes, and the mixture was allowed to stand for 5 minutes. After the ball milling was completed, the mixed material in the ball mill jars was scraped off to obtain Na2Li. 0.09 HfCl4O2N0.03 Materials (trace nitrogen-doped amorphous halide oxide solid electrolyte).
[0048] Example 2 A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte includes the following steps: In this embodiment, Na₂O₂ was used as the sodium and oxygen source, HfCl₄ as the hafnium and chlorine source, and Li₃N as the nitrogen source to synthesize Na₂Li. 0.21 HfCl4O2N 0.07 ; Na2O2, HfCl4, and Li3N raw materials were weighed according to a molar ratio of 1:1:0.07 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at 500 rpm for 8 hours. During the ball milling process, the mill was stopped for 5 minutes every 5 minutes, and the mixture was allowed to stand for 5 minutes. After the ball milling was completed, the mixed material in the ball mill jars was scraped off to obtain Na2Li. 0.21 HfCl4O2N 0.07 Materials (trace nitrogen-doped amorphous halide oxide solid electrolyte).
[0049] Example 3 A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte includes the following steps: In this embodiment, Na₂O₂ was used as the sodium and oxygen source, HfCl₄ as the hafnium and chlorine source, and Li₃N as the nitrogen source to synthesize Na₂Li. 0.36 HfCl4O2N 0.12 ; Na2O2, HfCl4, and Li3N raw materials were weighed in a molar ratio of 1:1:0.12 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at 500 rpm for 8 hours. During the ball milling process, the mill was stopped for 5 minutes every 5 minutes, and the mixture was allowed to stand for 5 minutes. After the ball milling was completed, the mixed material in the ball mill jars was scraped off to obtain Na2Li. 0.36 HfCl4O2N 0.12 Materials (trace nitrogen-doped amorphous halide oxide solid electrolyte).
[0050] Example 4 A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte includes the following steps: In this embodiment, Na₂O₂ was used as the sodium and oxygen source, ZrCl₄ as the zirconium and chlorine source, and Li₃N as the nitrogen source to synthesize Na₂Li. 0.09 ZrCl4O2N 0.03 ; Na2O2, ZrCl4, and Li3N raw materials were weighed in a molar ratio of 1:1:0.03 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at 500 rpm for 8 hours. During the ball milling process, the mill was stopped for 5 minutes every 5 minutes, and the mixture was allowed to stand for 5 minutes. After the ball milling was completed, the mixed material in the ball mill jars was scraped off to obtain Na2Li. 0.09 ZrCl4O2N 0.03 Materials (trace nitrogen-doped amorphous halide oxide solid electrolyte).
[0051] Example 5 A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte includes the following steps: In this embodiment, Na2O2 was used as the sodium and oxygen source, TaCl5 as the tantalum and chlorine source, and Li3N as the nitrogen source to synthesize NaLi. 0.21 TaCl5ON 0.07 ; Na2O2, TaCl5, and Li3N raw materials were weighed according to a molar ratio of 1:2:0.14 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at 500 rpm for 8 hours. During the ball milling process, the mill was stopped for 5 minutes every 5 minutes, and the mixture was allowed to stand for 5 minutes. After the ball milling was completed, the mixed material in the ball mill jars was scraped off to obtain NaLi. 0.21 TaCl5ON 0.07 Materials (trace nitrogen-doped amorphous halide oxide solid electrolyte).
[0052] Example 6 A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte includes the following steps: In this embodiment, Na₂O₂ was used as the sodium and oxygen source, NbCl₅ as the niobium and chlorine source, and Li₃N as the nitrogen source to synthesize Na₂Li. 0.21 NbCl5O2N 0.07 ; Na2O2, NbCl5, and Li3N raw materials were weighed according to a molar ratio of 1:1:0.07 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar; Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at 500 rpm for 8 hours. During the ball milling process, the mill was stopped for 5 minutes every 5 minutes, and the mixture was allowed to stand for 5 minutes. After the ball milling was completed, the mixed material in the ball mill jars was scraped off to obtain Na2Li. 0.21 NbCl5O2N 0.07 Materials (trace nitrogen-doped amorphous halide oxide solid electrolyte).
[0053] Comparative Example 1 Na2HfCl4O2 was synthesized by using Na2O2 as the sodium and oxygen source and HfCl4 as the hafnium and chlorine source. Na2O2 and HfCl4 raw materials were weighed at a molar ratio of 1:1 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar. Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at a speed of 500 rpm for 8 hours. After ball milling, the mixed material in the ball mill jars was scraped off to obtain Na2HfCl4O2 material.
[0054] Comparative Example 2 Na2ZrCl4O2 was synthesized by using Na2O2 as the sodium and oxygen source and ZrCl4 as the zirconium and chlorine source. Na2O2 and ZrCl4 raw materials were weighed at a molar ratio of 1:1 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar. Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at a speed of 500 rpm for 8 hours. After ball milling, the mixed material in the ball mill jars was scraped off to obtain Na2ZrCl4O2 material.
[0055] Comparative Example 3 Na2O2 was selected as the sodium and oxygen source, and TaCl5 as the tantalum and chlorine source to synthesize NaTaCl5O; Na2O2 and TaCl5 raw materials were weighed at a molar ratio of 1:2 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar. Two ball milling jars containing raw materials were sealed and placed in a high-energy ball mill at a speed of 500 rpm for 8 hours. After ball milling, the mixed material in the ball milling jars was scraped off to obtain NaTaCl5O material.
[0056] Comparative Example 4 Na2NbCl5O2 was synthesized by using Na2O2 as the sodium and oxygen source and NbCl5 as the niobium and chlorine source. Na2O2 and TaCl5 raw materials were weighed at a molar ratio of 1:1 and placed into a ball mill jar, with a total powder mass of 1 g in each ball mill jar. Two ball mill jars containing raw materials were sealed and placed in a high-energy ball mill at a speed of 500 rpm for 8 hours. After ball milling, the mixed material in the ball mill jars was scraped off to obtain Na2NbCl5O2 material.
[0057] Figure 1 Na2HfCl4O2 (Comparative Example 1), Na2Li0.09 HfCl4O2N 0.03 (Example 1) Na2Li 0.21 HfCl4O2N 0.07 (Example 2), Na2Li 0.36 HfCl4O2N 0.12 The XRD pattern of (Example 3) shows Na2HfCl4O2 and Na2Li. 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 All of them are completely amorphous structures and have no obvious XRD peaks.
[0058] Figure 2 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 Electrochemical impedance spectroscopy (EIS) was performed on solid-state electrolyte powders prepared in Examples 1-3 and Comparative Example 1. These powders were placed into a 10 mm diameter solid-state battery test mold and pressed into electrolyte sheets under a pressure of 10 MPa. During the test, the stainless steel pillars at both ends of the mold simultaneously contacted the electrolyte sheets and served as ion-blocking electrodes. The mold containing the electrolyte sheets was connected to a Biologic electrochemical workstation, and a 10 mV AC perturbation was applied at room temperature. The scanning frequency range was set to 1 Hz to 7 MHz, and AC impedance spectra of each sample were obtained. The resistance R of the electrolyte sheet was determined based on the impedance spectra, and the thickness L of the electrolyte sheet and the electrode contact area S were recorded. The room temperature ionic conductivity was calculated using σ = L / (R × S). The test results are as follows: Figure 3 As shown, the ionic conductivity of the comparative example Na2HfCl4O2 is 6.1 × 10⁻⁶. -4 S / cm; x=0.03, Na2Li 0.09 HfCl4O2N 0.03 Its ionic conductivity is 6.6 × 10⁻⁶. -4 S / cm; x=0.07, Na2Li 0.21 HfCl4O2N 0.07 The ionic conductivity was increased to 8.1 × 10⁻⁶. -4 S / cm; x continued to increase to 0.12, Na2Li 0.36 HfCl4O2N 0.12 The ionic conductivity decreased to 5.5 × 10⁻⁶. -4S / cm. These results indicate that the relationship between the amount of Li3N added and ionic conductivity is non-monotonic, with the sample at x=0.07 exhibiting the highest ionic conductivity in this test.
[0059] Figure 4 Na2ZrCl4O2, Na2Li 0.09 ZrCl4O2N 0.03 NaTaCl5O, NaLi 0.21 TaCl5ON 0.07 Na2NbCl5O2, Na2Li 0.21 NbCl5O2N 0.07 The ionic conductivity diagrams show that the ionic conductivity of each comparative example is improved after doping with trace amounts of Li3N.
[0060] Figure 5 Na2HfCl4O2 and Na2Li 0.21 HfCl4O2N 0.07 The electrochemical stability window plots show that there is no significant difference in the electrochemical stability windows of the two, both being greater than 4.3 V (vs. Na). 15 Sn4).
[0061] Na2Li at various temperatures 0.21 HfCl4O2N 0.07 From the ionic conductivity results, the Arrhenius curve can be plotted, and then the Na₂Li can be calculated. 0.21 HfCl4O2N 0.07 The activation energy is 0.314 eV, such as Figure 6 As shown.
[0062] Figure 7 Na2HfCl4O2, Na2Li 0.09 HfCl4O2N 0.03 Na2Li 0.21 HfCl4O2N 0.07 Na2Li 0.36 HfCl4O2N 0.12 The electronic conductivity of Na₂HfCl₄O₂ is 6.3 × 10⁻⁶. -10 Electronic conductivity S / cm, with the addition of a small amount of N 3- Na2Li 0.09 HfCl4O2N 0.03 Significantly reduced, with a value of 2.2 × 10⁻⁶. -10 Electronic conductivity of S / cm, further doped with N 3- Na2Li 0.21 HfCl4O2N 0.07The electronic conductivity increased slightly, reaching 6.1 × 10⁻⁶. -10 Electronic conductivity in S / cm, with excess N 3- Afterwards, Na2Li 0.36 HfCl4O2N 0.12 As the electronic conductivity increases, its electronic conductivity reaches its highest level, with a value of 8.7 × 10⁻⁶. -10 Electronic conductivity in S / cm.
[0063] Figure 8 Na2Li at a 0.5 C ratio 0.21 HfCl4O2N 0.07 The electrochemical performance can be seen from the figure. After 1300 cycles at 0.5 C, the material still exhibits a 37 mAh g⁻¹. -1 Specific capacity.
[0064] Figure 9 The figure shows the rate performance of the material at 0.1 C, 0.2 C, 0.3 C, 0.5 C, and 1 C. (Na₂Li) 0.21 HfCl4O2N 0.07 The highest specific capacity was found in Na₂Li, followed by Na₂Li. 0.09 HfCl4O2N 0.03 After cycling, almost all materials recovered their initial capacity at a 0.1 C rate, demonstrating that the materials all possess good stability. (Na₂Li) 0.21 HfCl4O2N 0.07 The material has good rate capability, and N 3- The introduction of this technology can stabilize the interface and maximize the positive electrode capacity.
[0065] In summary, this invention provides a trace nitrogen-doped amorphous halide oxide solid electrolyte, its preparation method, and its applications. This technical solution uses Na₂MCl… y Using O2 (M = Hf, Ta, Zr, Al, Nb)-based electrolytes as the matrix, where 3 ≤ y ≤ 5, trace amounts of N are innovatively introduced through precise component design and structural regulation. 3- , for O 2- Partial substitution at certain sites disrupts some bridging oxygen bonds, increasing the overall structural disorder. This trace nitrogen doping strategy has a significant effect on amorphous structures, thereby enabling the same material system to possess high ionic conductivity, good interfacial stability, and good mechanical properties.
[0066] This invention utilizes trace amounts of N 3- The system systematically optimizes the key properties of the electrolyte. N 3- Replace part of O 2-to break part of the bridging oxygen bonds, increase the degree of structural disorder, and ultimately effectively improve Na2Li 3x MCl y O2N x amorphous material (where M= Hf, Ta, Zr, Al, Nb) in terms of ionic conductivity, with 0<x≤0.12 and 3≤y≤5. The formation of the amorphous structure significantly improves the intrinsic flexibility of the material and optimizes the mechanical properties, making the material easier to achieve densification during the cold pressing process, thereby reducing the grain boundary impedance and improving the solid-solid contact with the electrode material. Benefiting from this, the ionic conductivity of the prepared solid electrolyte at room temperature is not less than 5×10 -4 S / cm, and reaches 8×10 in the preferred embodiment -4 S / cm or more, while the electronic conductivity is effectively suppressed to a level lower than 9×10 -10 S / cm, which ensures good sodium ion selective permeability.
[0067] The above content only illustrates the technical idea of the present invention, and shall not limit the protection scope of the present invention. Any modification made on the basis of the technical solution according to the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A trace nitrogen-doped amorphous halide oxide solid electrolyte, characterized in that, The solid electrolyte is an amorphous material, and the anion sites of the solid electrolyte are composed of O 2- and N 3- Jointly occupied, and N 3- The doping amount x satisfies 0 <x≤0.12; The chemical formula of the solid electrolyte is Na₂Li. 3x MCl y O2N x M is selected from at least one of Hf, Ta, Zr, Al or Nb, and 3≤y≤5.
2. The trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 1, characterized in that, The ionic conductivity of the solid electrolyte at room temperature is not less than 5 × 10⁻⁶. -4 S / cm, electronic conductivity less than 9×10 -10 S / cm, activation energy below 0.33 eV.
3. The trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 1, characterized in that, The ionic conductivity of the solid electrolyte at room temperature is not less than 8 × 10⁻⁶. -4 S / cm, electronic conductivity less than 6.1×10 -10 S / cm, activation energy below 0.32 eV, Young's modulus below 2.8 GPa, and electrochemical stability window greater than 4.3 V.
4. A method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte according to any one of claims 1 to 3, characterized in that, Includes the following steps: According to the general chemical formula Na₂Li 3x MCl y O2N x Sodium source, M source, chlorine source, oxygen source and nitrogen source are weighed as raw materials, the weighed raw materials are mixed, and ball milling is performed under inert atmosphere or vacuum protection to obtain the trace nitrogen-doped amorphous halide oxide solid electrolyte.
5. The method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 4, characterized in that, The sodium source is Na2O2; the M source is at least one of HfCl4, TaCl5, ZrCl4, AlCl3 and NbCl5.
6. The method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 4, characterized in that, The nitrogen source is Li3N; the oxygen source is Na2O2.
7. The method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 4, characterized in that, The chlorine source is MCl. y , where 3≤y≤5.
8. The method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 4, characterized in that, The ball milling process is performed at a speed of 200-1000 rpm for 5 minutes to 72 hours.
9. The method for preparing a trace nitrogen-doped amorphous halide oxide solid electrolyte according to claim 4, characterized in that, The ball milling process is intermittent, with a 5-minute stop and a 5-minute rest period after each 5-minute ball milling session.
10. The application of a trace nitrogen-doped amorphous halide oxide solid electrolyte according to any one of claims 1 to 3 in an all-solid-state battery.